Nonlocal correlations in the optical conductivity spectra - Dobushovskyi, D.A.; Shvaika, A.M. (Condensed Matter Physics, 2018)
Optical conductivity spectra are studied for the Falicov-Kimball model with correlated hopping on the Bethe lattice. An expression for the current-current correlation function is derived using dynamical mean field theory. In the metallic phase with small correlated hopping values, the shape of Drude peak deviates from the Debye relaxation peak, and an additional wide peak is observed on the optical conductivity spectra and on Nyquist plot when Fermi level is in the vicinity of the two particle resonance. At larger values of the correlated hopping parameter, the density of states contains three bands and the corresponding optical spectra and Nyquist plots display a more complicated shape with additional peaks. For strong local correlations, the correlated hopping reduces the width of the upper Hubbard band resulting in a decrease of the Drude peak spectral weight for the doped Mott insulator. Для моделi Фалiкова-Кiмбала з корельованим переносом на ґратцi Бете дослiджено спектри оптичної провiдностi. Використовуючи теорiю динамiчного середнього поля, отримано вирази для кореляцiйних функцiй струм-струм. В металiчнiй фазi i для малих значень корельованого переносу спостерiгається вiдхилення форми пiку Друде вiд дебаївської релаксацiї та виявлено появу додаткового широкого пiку на спектрах оптичної провiдностi i дiаграмах Найквiста, коли рiвень Фермi знаходиться поблизу двочастинкового резонансу. Для бiльших значень величини корельованого переносу, густина станiв мiстить три зони, а вiдповiднi оптичнi спектри та дiаграми Найквiста набувають складної форми з додатковими пiками. Для сильних локальних кореляцiй врахування корельованого переносу приводить до звуження верхньої хаббардiвської зони та зменшення спектральної ваги пiку Друде для легованих моттiвських дiелектрикiв.